Dose-response effects of acute exercise intensity on state anxiety among women with depression - Perkins, Seana L.; Cook, Dane B.; Herring, Matthew P.; Meyer, Jacob D. (Frontiers in Psychiatry, 2023)
Anxiety is common in people with major depressive disorder (MDD), yet the anxiolytic effects of acute exercise in MDD are unknown. The purpose of this analysis was to determine a potentially optimal acute exercise intensity for reducing state anxiety in women with MDD, the duration of the response, and the potential influences of depression severity and preferred-intensity exercise. Using a within-subject, randomized, counter-balanced design, 24 participants completed five separate visits including 20 minutes of steady-state bicycling at prescribed (via RPE) light, moderate, or hard intensities, a preferred/self-selected session, or a quiet rest (QR) session. State anxiety was measured via the State-Trait Anxiety Inventory (STAI-Y1) and anxiety visual analog scale (VAS) at pre-, immediately (VAS only), 10min, and 30min post-exercise. Depression was measured via the Beck Depression Inventory (BDI-II) pre-exercise. Moderate exercise resulted in a moderate state anxiety reduction compared to QR 10min (STAI-Y1: g=0.59, padj=0.040) and 30min post-exercise (STAI-Y1: g=0.61, padj=0.032). Pairwise differences indicated each exercise session decreased state anxiety pre to 10min and 30min post-exercise (all padj<0.05) for the STAI-Y1, and for moderate and hard exercise from pre to each time point post-exercise, (all padj<0.05) for the VAS. Depression severity was associated with state anxiety (p<0.01) but did not influence the overall results. Prescribed moderate intensity exercise led to greater reductions in state anxiety compared to preferred at 30m (STAI-Y1: g=0.43, p=0.04). These findings suggest steady-state prescribed moderate exercise reduces state anxiety in women with MDD for at least 30 minutes following exercise regardless of their depression severity.